Bacillus thuringiensis strain QBT220 pBtoxis plasmid structural instability enhances δ-endotoxins synthesis and bioinsecticidal activity - Kavita Nair (Elsevier, 2021)
Bacillus thuringiensis subsp. israelensis (Bti) spherical parasporal crystal contains several insecticidal proteins used as environmentally safe alternative to toxic chemical pesticides. The exploration of a Bti strain isolated from Qatar QBT220 genes encoding the δ-endotoxins responsible of the insecticidal activities revealed the alteration of a 14-kb DNA region including the δ-endotoxins cry10A and cyt1C genes of pBtoxis plasmid. The presence of all the insecticidal genes except cry10A and cyt1C was explained by a structural instability of the plasmid pBtoxis. However, when compared with the Bti reference strains H14 and QBT217 that carry all δ-endotoxins coding genes, it was found that QBT220, has a significantly higher insecticidal activity against the dipteran insect Aedes aegypti larvae despite of the plasmid pBtoxis structural instability due to the alteration of cry10A and cyt1C genes. In addition, QBT220 showed the highest δ-endotoxin synthesis per spore, compared with that of the wildtype strains. These findings confirm that the altered genes cry10A and cyt1C are not mandatory for Bti insecticidal activities and on the other hand show a possible inhibitory effect played by the 2 proteins Cry10A and Cyt1C on the insecticidal activities of the other insecticidal proteins. In addition, the QBT220 increased δ-endotoxins synthesis per cell, makes this strain a good candidate for possible applications in the industrial production of bioinsecticides.